The Role of Inertia and Dissipation in the Dynamics of the Director for a Nematic Liquid Crystal Coupled with an Electric Field (Communications in Computational Physics, 2018)
We consider the dynamics of the director in a nematic liquid crystal whenunder the influence of an applied electric field. Using an energy variational approachwe derive a dynamic model for the director including both dissipative and inertialforces.A numerical scheme for the model is proposed by extending a scheme for a relatedvariational wave equation. Numerical experiments are performed studying therealignment of the director field when applying a voltage difference over the liquidcrystal cell. In particular, we study how the relative strength of dissipative versus inertialforces influence the time scales of the transition between the initial configurationand the electrostatic equilibrium state.